The Helsinki Process and Germany (Czech Journal of International Relations, 1992)
The Parisian CSCE summit has meant a dividing line in the Helsinki process. The European Communities and NATO have to be considered the core of a unified Europe, and the basis for its prosperity, stability and security. The FRG plays a key-role in the Helsinki process. The whole-European attitude of both the EC and the transformed NATO are a pre-condition for its successful development. The so called Eastern Policy of the FRG which has a whole European dimension within the framework of CSCE is an organic part of these attitudes. The complicated and long-term process concerning the transformation of post-communist countries is that national extremism and uneven developments of Eastern and West Europe have to be solved, it is aimed at the creation of a union between all European countries and nationalities with equal rights in a unified, democratic and all-round prospering Europe, where regional and civil dimensions will be greatly enforced. The ČSFR and FRG relations have a specific role in these efforts.